2012
DOI: 10.4236/jct.2012.31014
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Knowledge and Handling Practice of Nurses Working in a Medical University of Nepal

Abstract: Background: Many antineoplastic agents are known to be teratogenic and mutagenic to humans. Nurses are the main groups that are exposed to these drugs in hospital setting. Generally, the occupational activities that pose to greatest risk of exposure are the preparation and administration of antineoplastic agents, cleaning of chemotherapy spills, and handling of patient excreta. Objective: The objectives of this study were to evaluate the knowledge of nurse regarding the way of exposure of Cytotoxic Drugs (CDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 11 publications
4
22
5
Order By: Relevance
“…As reported in the previous studies, participating in training programs significantly enhance the nurse's knowledge (16)(17)(18). The current study also showed a significant difference between knowledge scores of trained and untrained nurses regarding work in oncology ward.…”
Section: Knowledgesupporting
confidence: 48%
See 1 more Smart Citation
“…As reported in the previous studies, participating in training programs significantly enhance the nurse's knowledge (16)(17)(18). The current study also showed a significant difference between knowledge scores of trained and untrained nurses regarding work in oncology ward.…”
Section: Knowledgesupporting
confidence: 48%
“…U n c o r r e c t e d P r o o f score (17). Overall practice score was relatively appropriate, showing that oncology nurses may follow guideline instructions.…”
Section: Practicementioning
confidence: 95%
“…These finding are contradicted with Elshamy et al, (2010) [20] and Chaudhary and Karn, (2012) [14] who reported that fewer nurses mentioned that there are nursing care guidelines for procedures for dealing with patients receiving CDs as well as presence of in-service training programs. Also, Kyprianou, et al, (2010) [6] stated that most of the nurses were aware of the potential hazards of handling antineoplastic agents despite not having received specialized training on safe handling practices and they did not receive annual medical surveillance as a result of handling antineoplastic agents in their study that titled "Knowledge, attitudes and beliefs of Cypriot nurses on the handling of antineoplastic agents".…”
Section: P-value T-testcontrasting
confidence: 56%
“…This result is contradicted with Chaudhary and Karn, (2012) [14] who reported that no significant differences were found in the frequency of risky behaviors in working environment regarding CDs and none of the nurses were using the four protective equipments necessary during the handling of CDs in their study that titled "chemotherapy-knowledge and handling practice of nurses working in a medical university of Nepal". But in accordance with Bolbol, Hassan, El-Naggar and Zaitoun, (2016) [18] who reported that there is significant improvement in studied nurses' attitude and practice after intervention regarding the use of personal protective equipment during handling patients' waste and cleaning up spills.…”
Section: P-value T-testcontrasting
confidence: 55%
See 1 more Smart Citation